KEYPOINTS IN INVESTIGATING THE CHILD WITH GLOBAL DEVELOPMENTAL DELAY AND INTELLECTUAL DISABILITY - Diana Barca; Nina Butoianu; Oana Tarta-Arsene; Magdalena Budisteanu; Sanda Magureanu; Dana Craiu (Romanian Journal of Pediatrics, 2014)
Objective. This paper highlights the main lines of etiological investigation of global developmental delay (GDD), mental retardation (MR) or intellectual disability (ID) and their specifi c order. GDD and MR/ID are chronic entities with onset during the developmental period, affecting personal, social, academic, occupational functions. Elucidating the etiology is important for establishing the management, for assessing the outcome, the recurrence risk, potential opportunities for prevention and for decreasing the psycho-emotional impact on families. Material and method. Relevant literature was reviewed, currently being published recommendations for the diagnostic approach of children with GDD/MR, starting with a thorough history, a thorough clinical examination, then formulating a suspected etiology and including genetic, metabolic, neuroimaging testing. Results and conclusions. Advances in genetics have changed the approach of children with unexplained GDD, increasing the rate of pathogenic chromosomal abnormalities identifi cation. Comparative genomic hybridization is recommended as fi rst-line investigation, with karyotyping as complementary. Sequencing allows the study of many genes involved in GDD and genetic consultation prioritizes the investigations. The identifi cation of the etiologic diagnosis offers the possibility of establishing anticipatory, individualized management plans, in order to limit the complications and associated comorbidities, thereby improving the quality of life.